Penerapan International Cataloguing Principles pada Perpustakaan Nasional Republik Indonesia - Rahman Hidayat, Fandi; Mayesti, Nina (Universitas Islam Negeri Salatiga, 2024)
This paper discusses the application of the General Principles from the International Cataloguing Principles (ICP) in the cataloging process of information resources at the National Library of Indonesia. The study employs a qualitative method, with data collected from key informants within the institution. The objective is to assess whether the National Library of Indonesia, as the supervisory body for all types of libraries in Indonesia, adheres to the general rules established in the ICP. As a supervisory institution, the National Library of Indonesia is expected to set a good example for all libraries in Indonesia by effectively conducting the cataloging process for its collections. Additionally, this institution plays a crucial role in preserving Indonesia's library materials as evidence of the nation's history and civilization.